2021
DOI: 10.3389/fpsyt.2020.597789
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Dysregulation Moderates the Association Between Stress and Problematic Cannabis Use

Abstract: Background: Research suggests emotion dysregulation is a transdiagnostic risk factor for substance use and addiction and that stress may lead to problematic cannabis use. Thus, the current study examines how emotion dysregulation moderates the associations between stress (stressful life events and perceived stress) and problematic cannabis use.Methods: Eight hundred and fifty-two adults reporting any lifetime cannabis use completed an anonymous online survey. Participants completed a brief demographic question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
6
1
Order By: Relevance
“…Specifically, peer victimization positively predicted NSSI changes among adolescents with low ER difficulties, while the predictive effect was not significant at high ER difficulties. The results may seem contrary to previous studies on the interaction between stress and ER difficulties (Cavalli & Cservenka, 2021; Sui et al, 2020), but in fact, they add to each other. Previous studies that revealed an exacerbating effect of ER difficulties on the relationship between stress and NSSI primarily at the between‐person level (Voon et al, 2014), whereas within‐person relations could differ from between‐person associations (Zhu et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Specifically, peer victimization positively predicted NSSI changes among adolescents with low ER difficulties, while the predictive effect was not significant at high ER difficulties. The results may seem contrary to previous studies on the interaction between stress and ER difficulties (Cavalli & Cservenka, 2021; Sui et al, 2020), but in fact, they add to each other. Previous studies that revealed an exacerbating effect of ER difficulties on the relationship between stress and NSSI primarily at the between‐person level (Voon et al, 2014), whereas within‐person relations could differ from between‐person associations (Zhu et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…No main or moderating effects were found among problems with emotional clarity and the inability to control behaviors. Although existing research has indicated that ER difficulties could moderate the relationship between stress and mental health problems (Cavalli & Cservenka, 2021;Sui et al, 2020), there is still a relative lack of empirical studies directly examining the moderating role of ER difficulties in the relationship between peer victimization and NSSI. Using a longitudinal design, we examined how peer victimization and ER difficulties interact to shape changes in NSSI, with particular attention given to the specific moderating effects of the different dimensions of ER difficulties.…”
Section: Moderating Roles Of the Distinct Facets Of Er Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our context, problematic technology use itself can cause harm to those affected. Of interest for the present work: Negative life situations (such as stress) are closely related to emotion dysregulation and emotional disorders ( Cavalli & Cservenka, 2021 ; Schneider, Long, Arch, & Hankin, 2021 ). This may explain why adolescent emotion dysregulation is closely related to their problematic technology use, and emotion dysregulation may even be a predictor of adolescent problematic technology use, but this hypothesis needs to be supported by longitudinal research.…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing stressful life events and reporting higher perceived stress is associated with more CRNCs and were moderated by level of emotion dysregulation in one cross-sectional study. 56 Multiple forms of anxiety were investigated in relation to CRNCs; however, all studies were cross-sectional in nature. There is limited and mixed evidence to support social anxiety as a direct predictor of CRNCs.…”
Section: Resultsmentioning
confidence: 99%